A decrease in Fkbp52 alters autophagosome maturation and A152T-tau clearance in vivo - Lesport, Emilie; Commeau, Lucie; Genet, Mélanie; Baulieu, Etienne-Emile; Tawk, Marcel; Giustiniani, Julien (Frontiers in Cellular Neuroscience, 2024)
The failure of the autophagy-lysosomal pathway to clear the pathogenic forms of Tau exacerbates the pathogenesis of tauopathies. We have previously shown that the immunophilin FKBP52 interacts both physically and functionally with Tau, and that a decrease in FKBP52 protein levels is associated with Tau deposition in affected human brains. We have also shown that FKBP52 is physiologically present within the lysosomal system in healthy human neurons and that a decrease in FKBP52 expression alters perinuclear lysosomal positioning and Tau clearance during Tau-induced proteotoxic stress in vitro. In this study, we generate a zebrafish fkbp4 loss of function mutant and show that axonal retrograde trafficking of Lamp1 vesicles is altered in this mutant. Moreover, using our transgenic HuC::mCherry-EGFP-LC3 line, we demonstrate that the autophagic flux is impaired in fkbp4 mutant embryos, suggesting a role for Fkbp52 in the maturation of autophagic vesicles. Alterations in both axonal transport and autophagic flux are more evident in heterozygous rather than homozygous fkbp4 mutants. Finally, taking advantage of the previously described A152T-Tau transgenic fish, we show that the clearance of pathogenic A152T-Tau mutant proteins is slower in fkbp4 +/-mutants in comparison to fkbp4 +/+ larvae. Altogether, these results indicate that Fkbp52 is required for the normal trafficking and maturation of lysosomes and autophagic vacuoles along axons, and that its decrease is sufficient to hinder the clearance of pathogenic Tau in vivo.